Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
File size: 7,184 Bytes
4365a98
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
(* ========================================================================= *)
(* Some examples of full complex quantifier elimination.                     *)
(* ========================================================================= *)

let th = time prove
 (`!x y. (x pow 2 = Cx(&2)) /\ (y pow 2 = Cx(&3))
         ==> ((x * y) pow 2 = Cx(&6))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`!x a. (a pow 2 = Cx(&2)) /\ (x pow 2 + a * x + Cx(&1) = Cx(&0))
         ==> (x pow 4 + Cx(&1) = Cx(&0))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`!a x. (a pow 2 = Cx(&2)) /\ (x pow 2 + a * x + Cx(&1) = Cx(&0))
         ==> (x pow 4 + Cx(&1) = Cx(&0))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`~(?a x y. (a pow 2 = Cx(&2)) /\
             (x pow 2 + a * x + Cx(&1) = Cx(&0)) /\
             (y * (x pow 4 + Cx(&1)) + Cx(&1) = Cx(&0)))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`!x. ?y. x pow 2 = y pow 3`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`!x y z a b. (a + b) * (x - y + z) - (a - b) * (x + y + z) =
               Cx(&2) * (b * x + b * z - a * y)`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`!a b. ~(a = b) ==> ?x y. (y * x pow 2 = a) /\ (y * x pow 2 + x = b)`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`!a b c x y. (a * x pow 2 + b * x + c = Cx(&0)) /\
               (a * y pow 2 + b * y + c = Cx(&0)) /\
               ~(x = y)
               ==> (a * x * y = c) /\ (a * (x + y) + b = Cx(&0))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

let th = time prove
 (`~(!a b c x y. (a * x pow 2 + b * x + c = Cx(&0)) /\
                 (a * y pow 2 + b * y + c = Cx(&0))
                 ==> (a * x * y = c) /\ (a * (x + y) + b = Cx(&0)))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

(** geometric example from ``Algorithms for Computer Algebra'':
    right triangle where perp. bisector of hypotenuse passes through the
    right angle is isoseles.
 **)

let th = time prove
 (`!y_1 y_2 y_3 y_4.
     (y_1 = Cx(&2) * y_3) /\
     (y_2 = Cx(&2) * y_4) /\
     (y_1 * y_3 = y_2 * y_4)
     ==> (y_1 pow 2 = y_2 pow 2)`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

(** geometric example: gradient condition for two lines to be non-parallel.
 **)

let th = time prove
 (`!a1 b1 c1 a2 b2 c2.
        ~(a1 * b2 = a2 * b1)
        ==> ?x y. (a1 * x + b1 * y = c1) /\ (a2 * x + b2 * y = c2)`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

(*********** Apparently takes too long

let th = time prove
 (`!a b c x y. (a * x pow 2 + b * x + c = Cx(&0)) /\
               (a * y pow 2 + b * y + c = Cx(&0)) /\
               (!z. (a * z pow 2 + b * z + c = Cx(&0))
                    ==> (z = x) \/ (z = y))
               ==> (a * x * y = c) /\ (a * (x + y) + b = Cx(&0))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

*************)

(* ------------------------------------------------------------------------- *)
(* Any three points determine a circle. Not true in complex number version!  *)
(* ------------------------------------------------------------------------- *)

(******** And it takes a lot of memory!

let th = time prove
 (`~(!x1 y1 x2 y2 x3 y3.
        ?x0 y0. ((x1 - x0) pow 2 + (y1 - y0) pow 2 =
                 (x2 - x0) pow 2 + (y2 - y0) pow 2) /\
                ((x2 - x0) pow 2 + (y2 - y0) pow 2 =
                 (x3 - x0) pow 2 + (y3 - y0) pow 2))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

 **************)

(* ------------------------------------------------------------------------- *)
(* To show we don't need to consider only closed formulas.                   *)
(* Can eliminate some, then deal with the rest manually and painfully.       *)
(* ------------------------------------------------------------------------- *)

let th = time prove
 (`(?x y. (a * x pow 2 + b * x + c = Cx(&0)) /\
          (a * y pow 2 + b * y + c = Cx(&0)) /\
          ~(x = y)) <=>
   (a = Cx(&0)) /\ (b = Cx(&0)) /\ (c = Cx(&0)) \/
   ~(a = Cx(&0)) /\ ~(b pow 2 = Cx(&4) * a * c)`,
  CONV_TAC(LAND_CONV FULL_COMPLEX_QUELIM_CONV) THEN
  REWRITE_TAC[poly; COMPLEX_MUL_RZERO; COMPLEX_ADD_LID; COMPLEX_ADD_RID] THEN
  REWRITE_TAC[COMPLEX_ENTIRE; CX_INJ; REAL_OF_NUM_EQ; ARITH] THEN
  ASM_CASES_TAC `a = Cx(&0)` THEN
  ASM_REWRITE_TAC[COMPLEX_MUL_LZERO; COMPLEX_MUL_RZERO] THENL
   [ASM_CASES_TAC `b = Cx(&0)` THEN
    ASM_REWRITE_TAC[COMPLEX_MUL_LZERO; COMPLEX_MUL_RZERO];
    ONCE_REWRITE_TAC[SIMPLE_COMPLEX_ARITH
     `b * b * c * Cx(--(&1)) + a * c * c * Cx(&4) =
      c * (Cx(&4) * a * c - b * b)`] THEN
    ONCE_REWRITE_TAC[SIMPLE_COMPLEX_ARITH
     `b * b * b * Cx(--(&1)) + a * b * c * Cx (&4) =
      b * (Cx(&4) * a * c - b * b)`] THEN
    ONCE_REWRITE_TAC[SIMPLE_COMPLEX_ARITH
     `b * b * Cx (&1) + a * c * Cx(--(&4)) =
      Cx(--(&1)) * (Cx(&4) * a * c - b * b)`] THEN
    REWRITE_TAC[COMPLEX_ENTIRE; COMPLEX_SUB_0; CX_INJ] THEN
    CONV_TAC REAL_RAT_REDUCE_CONV THEN
    ASM_CASES_TAC `b = Cx(&0)` THEN ASM_REWRITE_TAC[] THEN
    ASM_CASES_TAC `c = Cx(&0)` THEN ASM_REWRITE_TAC[] THEN
    REWRITE_TAC[COMPLEX_POW_2; COMPLEX_MUL_RZERO; COMPLEX_MUL_LZERO] THEN
    REWRITE_TAC[EQ_SYM_EQ]]);;

(* ------------------------------------------------------------------------- *)
(* Do the same thing directly.                                               *)
(* ------------------------------------------------------------------------- *)

(**** This seems barely feasible

let th = time prove
 (`!a b c.
      (?x y. (a * x pow 2 + b * x + c = Cx(&0)) /\
             (a * y pow 2 + b * y + c = Cx(&0)) /\
             ~(x = y)) <=>
      (a = Cx(&0)) /\ (b = Cx(&0)) /\ (c = Cx(&0)) \/
      ~(a = Cx(&0)) /\ ~(b pow 2 = Cx(&4) * a * c)`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

 ****)

(* ------------------------------------------------------------------------- *)
(* More ambitious: determine a unique circle. Also not true over complexes.  *)
(* (consider the points (k, k i) where i is the imaginary unit...)           *)
(* ------------------------------------------------------------------------- *)

(********** Takes too long, I think, and too much memory too

let th = prove
 (`~(!x1 y1 x2 y2 x3 y3 x0 y0 x0' y0'.
        ((x1 - x0) pow 2 + (y1 - y0) pow 2 =
         (x2 - x0) pow 2 + (y2 - y0) pow 2) /\
        ((x2 - x0) pow 2 + (y2 - y0) pow 2 =
         (x3 - x0) pow 2 + (y3 - y0) pow 2) /\
        ((x1 - x0') pow 2 + (y1 - y0') pow 2 =
         (x2 - x0') pow 2 + (y2 - y0') pow 2) /\
        ((x2 - x0') pow 2 + (y2 - y0') pow 2 =
         (x3 - x0') pow 2 + (y3 - y0') pow 2)
        ==> (x0 = x0') /\ (y0 = y0'))`,
  CONV_TAC FULL_COMPLEX_QUELIM_CONV);;

 *************)

(* ------------------------------------------------------------------------- *)
(* Side of a triangle in terms of its bisectors; Kapur survey 5.1.           *)
(* ------------------------------------------------------------------------- *)

(*************
let th = time FULL_COMPLEX_QUELIM_CONV
 `?b c. (p1 = ai pow 2 * (b + c) pow 2 - c * b * (c + b - a) * (c + b + a)) /\
        (p2 = ae pow 2 * (c - b) pow 2 - c * b * (a + b - c) * (a - b + a)) /\
        (p3 = be pow 2 * (c - a) pow 2 - a * c * (a + b - c) * (c + b - a))`;;

 *************)